2007
DOI: 10.4049/jimmunol.179.7.4884
|View full text |Cite
|
Sign up to set email alerts
|

Elf-1 Binds to GGAA Elements on the FcRγ Promoter and Represses Its Expression

Abstract: The Fc receptor (FcR) γ-chain has been shown to be up-regulated in T cells when the TCR ζ-chain is decreased. We demonstrate that Elf-1, but not other Ets family transcription factors, bind to a cluster of GGAA sites located within the 200 bp upstream from the transcription initiation site of the FcRγ promoter. Forced expression of Elf-1 results in the suppression of FcRγ expression, whereas silencing its expression with small interfering RNA Elf-1 results in increased FcRγ expression. Elf-1 represents the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Therefore, the ratio of expression levels of GABP and Elf-1, which differs depending on cell types or conditions, might affect the expression level of FcR␥. Consistent with this, Juang et al (34) recently reported that Elf-1 bound to GGAA elements on the FcR␥ promoter and repressed its expression. In their study, Elf-1 bound to multiple elements, including motif A in the region of nt Ϫ141/Ϫ66 (corresponding to nt Ϫ121/Ϫ46 in their study), whereas Sp1 bound to motif A in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, the ratio of expression levels of GABP and Elf-1, which differs depending on cell types or conditions, might affect the expression level of FcR␥. Consistent with this, Juang et al (34) recently reported that Elf-1 bound to GGAA elements on the FcR␥ promoter and repressed its expression. In their study, Elf-1 bound to multiple elements, including motif A in the region of nt Ϫ141/Ϫ66 (corresponding to nt Ϫ121/Ϫ46 in their study), whereas Sp1 bound to motif A in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Recently however, Juang and colleagues reported that Elf-1, a member of the Ets family of transcription factors, is a negative transcriptional regulator of FcRγ in human T lymphocytes whereas it is a positive transcriptional regulator for TCRζ in the same cells [27], [28]. Neither the role of Elf-1 in FcRγ expression in NK cells nor the effect of HIV-1 infection on Elf-1 expression is known.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, TCR engagement causes one abnormality (for example, lipid raft aggregation) that linearly elicits the others. We should note that decreased expression of the DNA-binding form of the transcription factor Elf-1 results both in decreased activity of the TCRz promoter [11] and increased activity of the FcRg promoter [21], explaining, in part, the presence of FcRg and the reciprocal decrease of CD3z in SLE T cells.…”
Section: Upregulated Adhesion Molecules Guide T Cells To Tissuesmentioning
confidence: 99%